"I love you guys": Hoosiers as a model for transformational and limited transactional coaching. Issue 1 (25th March 2016) - Mead, Bryan; Mead, Jason
Abstract: This interpretive paper explores the relationship between real-world athletic coaching practices and cinematic coaching practices to gauge the sports film's potential as a coaching aid. Our analysis suggests the leadership decisions of Norman Dale, fictitious coach of the Hickory High School basketball team in the movie Hoosiers, aligns very closely with the five leadership principles and decisions published by Kouzes and Posner. These connections make Hoosiers, despite obvious cinematic simplifications, an instructional model for novice and beginning coaches looking to implement transformational and limited transactional coaching practices.